Efficacy and Application Prospect of Ginger Oil with Ginger Characteristics - LI Tong; WANG Yuan-li; GUO Mi-mi; YANG Kai-zhou; LUAN Xia (Liang you shipin ke-ji, 2020)
Ginger essential oil is the main deep-processed product of ginger. Ginger oil has functional properties, such as anti-oxidation and anti-inflammatory, because of the upgrade of extraction technology.Ginger is widely used in the pharmaceutical and cosmetic industries because of its rich in phenols. Ginger oil not only inherits the function of removing fishy smell, but also retains the health benefits of ginger. With consumers' attention to health, the application of ginger oil in cooking is also concerned. This article compared the advantages and disadvantages of various ginger oil extraction methods, summarized the benefits of ginger oil, and prospected the application of ginger oil based on internal and external R & D and market situation.